Gallstone Ileus: Uncommon Presentation Followed by Less Common Spontaneous Resolution - Hobbs, Nicholas (Cureus, 2020)
Gallstone ileus is a rare but significant cause of bowel obstruction. An 82-year-old female was admitted to the hospital with abdominal pain and was initially treated for a possible urinary tract infection. Following a surgical review and based on history, clinical examination as well as radiological findings, a diagnosis of gallstone ileus was made. The patient was prepared for surgery; however, whilst awaiting theatre, she spontaneously passed the obstructing gallstone with full resolution of bowel obstruction symptoms. The usual treatment for gallstone ileus is surgical management with an enterolithotomy; nevertheless, this case highlights the importance of close monitoring and adapting a management plan to fit an evolving clinical scenario.